Yertle the Turtle, and Other Stories - Seuss Dr. (New York, Random House, 1958)
3 popular tales by the famous Dr. Seuss which teach a lesson about the consequences of being thoughtless, vain, and conceited.
Keywords: Stories in rhyme; Fantasy